PENDIDIKAN HUKUM PERSPEKTIF AL-QUR’AN DAN HADITS - Khairy Abusyairi; Iskandar (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2021)
The Qur'an as a book of guidance, is full of verses that regulate the behavior and attitudes of the children of Adam. Not only in terms of the vertical relationship between humans and Allah SWT as the Creator, but also in the horizontal relationship between human beings with one another as fellow creatures. The verses of the Qur'an that regulate the vertical relationship between humans and Allah SWT are commonly referred to as verses of the law of worship. Meanwhile, the verses that regulate horizontal interaction between human beings are known as the legal verses of muamalah. Unfortunately, the legal verses in the Qur'an in general and in their entirety have not received adequate attention. This paper discusses verses related to law in the Qur'an and hadith. This discussion is explored with library studies. It is hoped that this paper can provide an overview of legal education from the perspective of the Qur'an and hadith